Lightweight multi-coupon system for multi-merchant environments with DAA - Xin LIU; Qiu-liang XU; Bo ZHANG (Tongxin xuebao)
A multi-coupon system for multi-merchant environments was proposed by extending the DAA (direct anonymous attestation) scheme of Brickell etc.The new system bound the key elements in multi-coupon with the tamper-resistant TPM（trusted platform module）chip,so that it could prevent users from sharing behavior more effectively.By using the server-aided signature verification of Chow etc,the self-blindable credential technique of Yang etc,and range proof of Peng etc,the new system does not require customers to perform expensive pairing operations in the issue protocol and the redeem protocol.Compared with previous similar systems,the new system simultaneously satisfies several ideal properties and it is compatible with the mobile payment framework on the ARM TrustZone platform.Moreover,it has obvious advantages in aspects of communication and computation costs.